Geoarkeologi Kebencanaan untuk Mendukung Pencapaian Tujuan Pembangunan Berkelanjutan - Purna Sulastya Putra; Eko Yulianto; Septriono Hari Nugroho; Yuka Nurtanti Cahyaningtyas; Agus Men Riyanto; Yayat Sudrajat; Januar Ridwan; Amar Amar (Badan Riset dan Inovasi Nasional (BRIN), 2022)
Many archeological sites that exist today are associated with catastrophic events in the past. Some archeological remains were found buried in volcanic ash materials, flood deposits, and even it related to tsunami that was happened in the past. For example, a paleotsunami research that was conducted in the western coast of Aceh has identified that one of the paleotsunami occurance which happened in 15th century might have responsible for the cultural hiatus in the northern of Sumatra during that century. It was hypothesized that the 15th century’s tsunami destroyed the pre-15th century civilizations and cultures. Unfortunately, the study of disaster geoarcheology especially in Indonesia is not a popular research topic, the connection between the archeological remains with the occurrence of disaster is still not properly discovered. Through the geoarcheological studies, not only the community response to the disaster can be identified but also the recurrence interval of the disaster can be predicted. For example, in Simeuleu, Aceh, the local wisdom of smong, a tradition that still exists today, has been proven to save many lives from tsunamis. In this paper, examples of geoarcheological studies will be discussed. Our understanding of the history of the archeological sites and their connection with the disaster is an important aspect and this information must be applied for the disaster mitigation and expected to be able to support achieving the goal of sustainable development.